Recanalisation of cerebral venous thrombosis. Issue 4 (1st April 2003) - Baumgartner, R W; Studer, A; Arnold, M; Georgiadis, D
Abstract : Objective: To investigate recanalisation in the first 12 months after cerebral venous thrombosis. Methods: 33 consecutive patients presenting with cerebral venous thrombosis were enrolled in the study. Diagnosis was made by magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) or catheter angiography. Patients were initially treated with intravenous heparin. Warfarin was given for at least four months. Cerebral MRI and MRV were done at four months and repeated after 12 months if venous thrombosis persisted. Outcome was evaluated by the Rankin scale at 12 months. Results: Outcome at 12 months was good, with a median modified Rankin scale score of 0 (range 0 to 2); 27 patients (82%) had no residual deficits. No patient suffered recurrent cerebral venous thrombosis, deep vein thrombosis, or pulmonary embolism during follow up. After four months, all deep cerebral veins and cavernous sinuses, 94% of superior sagittal sinuses, 80% of straight sinuses, 73% of jugular veins, 58% of transverse sinuses, and 41% of sigmoid sinuses had recanalised. No further recanalisation was observed thereafter. Conclusions: The results suggest that recanalisation only occurs within the first four months following cerebral venous thrombosis and not thereafter, irrespective of oral anticoagulation.